Blood pressure patterns of hypertensive disorders of pregnancy in first and second trimester and contributing factors: a retrospective study - Jie Ren; Zhuoran Fan; Jing Li; Yujie Wang; Junnong Zhang; Shaofang Hua (Taylor & Francis Group, 2023)
We aimed to investigate the blood pressure (BP) patterns of hypertensive disorders of pregnancy (HDP) in the first and second trimesters and its contributing factors, which may help us understand its pathogenesis and identify this group of diseases in a timely manner. SPSS 21.0 was used to describe the BP patterns of 688 HDP as well as 2050 normotensive pregnancies respectively before 28 gestational weeks, and the repeated measurements and two-way ANOVA was used to decide the significant difference of blood pressure in the same period. The results revealed blood pressure in HDP underwent a mid-pregnancy drop as normal while the drop was unremarkable in advanced-age or obesity pregnancies. Besides, we found blood pressure was significantly higher in patients during first and second trimesters, not just after 20 weeks. In conclusion, our study indicated a significant elevation of blood pressure had appeared before 20 weeks in HDP pregnancies, we should pay more attention to monitoring blood pressure before 20 weeks, especially for advanced age and obese women.IMPACT STATEMENT What is already known on this subject? Gestational hypertension, preeclampsia as well as eclampsia were supposed to have the similar pathogenesis and their time of onset was strictly defined after 20 gestational weeks, while the reason for the time point was not clear. On the other hand, higher blood pressure in the first trimester was associated with increasing risk of developing HDP, while the blood pressure(BP) pattern of normal as well as HDP pregnancy was still controversial, especially for the existence of mid-trimester drop. What do the results of this study add? Firstly, we found blood pressure in HDP underwent a mid-pregnancy drop as normal while the BP drop was unremarkable in advanced-age or obesity pregnancies. Secondly, we noticed the blood pressure in HDP was significantly higher than the normal before 20 weeks, which had not been proved before. What are the implications of these findings for clinical practice and/or further research? On one hand, both the abnormal elevation of BP and the development of the placenta happened in the first trimester suggested toxic substances caused by the defective placenta played a vital role in the onset and aggravation of HDP, which guides us to pay more attention to monitor blood pressure before 20 weeks, especially for advanced age and obesity pregnancies. On the other hand, our results about BP patterns in HDP help us identify this group of diseases in time which can contribute to a better outcome.